2019
DOI: 10.1002/admt.201900511
|View full text |Cite
|
Sign up to set email alerts
|

Kirigami‐Inspired Textile Electronics: K.I.T.E.

Abstract: Electronic textiles (e‐textiles) are in prime position to revolutionize the field of wearable electronics owing to their ubiquitous use and universal acceptance. However, mechanical incompatibility between the rigid conductive components on the soft textile platforms creates fragile e‐textile systems with poor electromechanical attributes. In this work, a novel design strategy to inkjet print reactive silver inks onto woven textiles with Kirigami‐inspired patterning to create e‐textiles with enhanced electrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…For instance, stretchable polymer substrate such as silicone‐based substrates, [ 56,200 ] textile‐based substrates, [ 201 ] and protein‐based substrates [ 202 ] had been investigated and elastic composites such as PDMS−ECCs, [ 102 ] AgNWs–PDMS mixtures, [ 103 ] and Ag‐PU nanocomposites [ 101 ] had been synthesized. Regarding structural design, typical deformable structures such as filamentary serpentine, [ 203 ] wrinkles, [ 60 ] and kirigami [ 204 ] have been implemented. With those strategies, on‐skin electrodes had achieved outstanding stretchability of over 400%.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…For instance, stretchable polymer substrate such as silicone‐based substrates, [ 56,200 ] textile‐based substrates, [ 201 ] and protein‐based substrates [ 202 ] had been investigated and elastic composites such as PDMS−ECCs, [ 102 ] AgNWs–PDMS mixtures, [ 103 ] and Ag‐PU nanocomposites [ 101 ] had been synthesized. Regarding structural design, typical deformable structures such as filamentary serpentine, [ 203 ] wrinkles, [ 60 ] and kirigami [ 204 ] have been implemented. With those strategies, on‐skin electrodes had achieved outstanding stretchability of over 400%.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Both natural and synthetic fiber-based substrates and their blend have been widely utilized as substrates for printing electrode [ 80 82 ]. Although earlier electrodes used to be printed on nonwoven fabrics, later woven fabrics and recently knitted fabrics are used as a substrate for wearable electrode fabrication [ 80 , 83 , 84 ]. The conductivity of printed traces on textile substrates depends on fiber diameter, porosity, surface energy, and tightness factor [ 80 ] and is often tailored as required for desired applications.…”
Section: Flexible Architectures For Printed Electrode Fabricationmentioning
confidence: 99%
“…The feasibility of the process while maintaining inherent stretchability, breathability, and comfort was also studied [ 145 ]. Li et al (2018) demonstrated an interesting approach by combining inkjet printing of silver ink with Kirigami patterning to tackle the issue of mechanical dissimilarities between the textile substrate and the ink [ 83 ]. This Kirigami-inspired textile electrode was formed by printing ink on PET woven fabric followed by laser cutting of Kirigami pattern and led to a softer mechanical response by decreasing elastic modulus and enhancing stretchability.…”
Section: Flexible Electrode Fabrication By Various Printing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The state-of-the-art practice of cutting, folding, bending, and twisting flat objects into versatile shapes, named kirigami or origami (origami does not include the cutting process) 1 , 2 , has recently arisen as a facile and automated fashion of three-dimensional (3D) manufacturing 3 7 . The fascinating transformation of two-dimensional (2D) precursors into complex 3D architectures has enabled exceptional geometries and functionalities 8 , 9 , which arouses great interests in the areas of microelectromechanical systems (MEMS) 10 13 , extraordinary mechanics 14 16 , biomedical devices 17 , acoustic materials 18 , energy storage systems 19 , 20 , microwave metamaterials 21 , 22 , and terahertz spectroscopy 23 . Particularly in the microscale/nanoscale region, kirigami/origami has achieved artful 3D nanomanufacturing 6 , 24 without the need of spatial translation 25 , 26 or multilayer stacking 27 in traditional on-chip 3D microfabrications.…”
Section: Introductionmentioning
confidence: 99%